Las claves del recuerdo.: El escudo de armas de los Enríquez en Santa Clara de Palencia como presencia efectiva - Carrión-Longarela, María (Eikón / Imago, 2025)
What became of the Enríquez family, admirals of Castile? What became of the ship-shaped tomb that the sources recall? Although it is still lost, other visual media maintain their memory in the family pantheon located in the convent of Santa Clara in Palencia. The heraldic device occupies a prominent role in this space, both in the north portal and especially in the interior of the church, where the keystones of the vaults stand out. The Enriquez coat of arms is repeatedly displayed on them, accompanied by those of the admirals’ wives. Taking the concept of the coat of arms as a medial face (H.Belting) as the reference point, the aim is to analyse the case of the pantheon of the Enriquez family. The topography of the church refines the message of the coats of arms and supports the construction of an image of the lineage’s power projected towards the city. Likewise, given the unknowns about the tomb, the testamentary mandates of the admirals give great importance to heraldry and suggest that the image they wanted for posterity should present them first as members of the lineage of the admirals, through the corporate portrait of the coats of arms, rather than as individualised faces.